Stochastic Modeling of Multiwavelength Variability of the Classical BL Lac Object OJ287 on Timescales Ranging from Decades to Hours - Goyal A (IOP PUBLISHING LTD, 2022)
We present the results of our power spectral density analysis for the BL Lac object OJ 287, utilizing the Fermi-LAT survey at high-energy.-rays, Swift-XRT in X-rays, several ground-based telescopes and the Kepler satellite in the optical, and radio telescopes at GHz frequencies. The light curves are modeled in terms of continuous-time autoregressive moving average (CARMA) processes. Owing to the inclusion of the Kepler data, we were able to construct for the first time the optical variability power spectrum of a blazar without any gaps across similar to 6 dex in temporal frequencies. Our analysis reveals that the radio power spectra are of a colored-noise type on timescales ranging from tens of years down to months, with no evidence for breaks or other spectral features. The overall optical power spectrum is also consistent with a colored noise on the variability timescales ranging from 117 years down to hours, with no hints of any quasi-periodic oscillations. The X-ray power spectrum resembles the radio and optical power spectra on the analogous timescales ranging from tens of years down to months. Finally, the.-ray power spectrum is noticeably different from the radio, optical, and X-ray power spectra of the source: we have detected a characteristic relaxation timescale in the Fermi-LAT data, corresponding to similar to 150 days, such that on timescales longer than this, the power spectrum is consistent with uncorrelated (white) noise, while on shorter variability timescales there is correlated (colored) noise.